2008
DOI: 10.1007/s10802-008-9278-9
|View full text |Cite
|
Sign up to set email alerts
|

A Common Genetic Factor Explains the Covariation Among ADHD ODD and CD Symptoms in 9–10 Year Old Boys and Girls

Abstract: Previous studies examining the covariation among Attention Deficit Hyperactivity Disorder (ADHD), Oppositional Defiant Disorder (ODD) and Conduct Disorder (CD) have yielded inconsistent results. Some studies have concluded that the covariation among these symptoms is due to common genetic influences, whereas others have found a common environmental overlap. The present study investigated the genetic and environmental correlations among these three childhood disorders, based on a sample of 1,241 twins, age 9-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 65 publications
(101 reference statements)
14
99
3
2
Order By: Relevance
“…As discussed above, this is consistent with wellreplicated findings from behavioral genetics studies conducted with children, adolescents, and adults (e.g., Caspi et al, 2014;Krueger et al, 2002;Tuvblad et al, 2009;Wright et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 86%
See 1 more Smart Citation
“…As discussed above, this is consistent with wellreplicated findings from behavioral genetics studies conducted with children, adolescents, and adults (e.g., Caspi et al, 2014;Krueger et al, 2002;Tuvblad et al, 2009;Wright et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 86%
“…measured both directly among children and via low constraint among adults), ODD, and CD (e.g.,Lahey, Van Hulle, Singh, Waldman, & Rathouz, 2011;Tuvblad, Zheng, Raine, & Baker, 2009). More recent work…”
mentioning
confidence: 99%
“…Consistent with a major thesis of this article, twin studies indicate that both internalizing and externalizing liabilities are highly heritable, but that specific behavioral syndromes are shaped considerably by environments (Krueger et al, 2002;Lahey et al, 2011;Tuvblad et al, 2009). Thus, whether a child who inherits trait impulsivity (i.e., liability to externalizing disorders; see Beauchaine & McNulty, 2013) develops ADHD or more serious externalizing conduct depends largely on environmental experience (see Figure 1).…”
Section: Integrate Emotion Dysregulation Into Factor Analytic and Behsupporting
confidence: 75%
“…The externalizing factor included alcohol dependence, drug dependence, and antisocial personality disorder. Additional factor analyses conducted since provide support for Krueger's initial findings (e.g., Krueger, Markon, Patrick, Benning, & Kramer, 2007;Krueger et al, 2002) and extend the externalizing factor to include hyperactivity=impulsivity, oppositional defiant disorder, and conduct disorder (e.g., Lahey, Van Hulle, Singh, Waldman, & Rathouz, 2011;Tuvblad, Zheng, Raine, & Baker, 2009). More recent work demonstrates that thought disorder emerges as a third higher order factor when psychotic symptoms are included (e.g., Wright et al, 2013).…”
Section: Integrate Emotion Dysregulation Into Factor Analytic and Behmentioning
confidence: 54%
“…Studies that have been conducted to explore these types of issues tend to employ bivariate genetic modeling techniques to estimate the proportion of covariance between two measures that is the result of genetic factors common to both phenotypes. A line of research using bivariate genetic modeling techniques has found shared genetic factors to explain the covariance between ADHD and measures of conduct disorder, oppositional defiant disorder, aggression, and violence [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%